Relationship between photosynthetically active radiation with global solar radiation using empirical model over selected climatic zones in Nigeria - Chukwujindu, Nwokolo Samuel; Julie C., Ogbulezie; Alwell, John-Jaja Sylvia (International Journal of Physical Research, 2017)
In this study, relationship between photosynthetically active radiation (PAR) and global solar radiation (H) over selected climatic zones in Nigeria using 22-years data (July 1983 – June 2005) was analysed. Empirical model was employed as the baseline for theoretical formulation and estimation of the ratio of PAR/H over climatic zones in Nigeria. From the estimated values, the seasonal PAR/H ranged from 1.946-2.005, 1.909-1.955, 1.968-2.039, 1.987-2.060, 1.961-2.041, 1.928-1.984 and 1.946-2.005 in rainy season, and the high values were due to low influence from clearness index, harmattan dust and pyrogenic aerosols from regional biomass burning compared with 1.906-1.923, 1.905-1.917, 1.927-1.952, 1.950-1.999, 1.971-1.985 and 1.889-1.923 recorded in dry season as a result of combined high influence from cloudiness, pyogenic aerosols and harmattan dust with annual mean values of 1.943, 1.921, 1.975, 2.007, 1.986 and 1.936 for Ilorin, Sokoto, Abeokuta, Port Harcourt, Enugu and Gusau respectively. The annual ratio of PAR/H revealed that there is an evidence increase of the values from North-East (Gusau) to South-South (Port Harcourt). These variations were mainly due to trends in cloudiness and associated atmospheric moisture with the movement of the Hadley cell circulation system along the equatorial line. From the analysed results, the model was found suitable and meteorologically reliable to estimate PAR/H accurately from commonly available H data when compared with results within and beyond tropical locations in Nigeria.